AZERBAYCAN'IN OSMANLI DEVLETİ SONRASINDA YENİDEN YAPILANMA SÜRECİ (1918-1953) - VERDIYEV, TURAL (Fırat Üniveristesi, 2018)
Giriş bölümünde 1918 yılına kadar Azerbaycan tarihi ve Osmanlı devleti sonrasında yeniden yapılanma süresiyle (1918-1953) ilgili genel bilgiler verdik ve tezin tanıtımını yaptık. Daha sonra 1918 yılına kadar olan gelişmeler, 1918-1953 yıllarında Azerbaycan'ın politik, ekonomik, kültürel yapılanmasından bahsettik. En sonda tezde kullanılan kaynakların listesini verdik.

Firstly, in introductory chapter we have given information about the Azerbaijan History until 1918 year and also about reconstruction process of Azerbaijan at the end of the Ottoman empire (1918-1953) and also promoted the thesis. Secondly, in main chapter we have given information events up to 1918 and political, economic and cultural reconstruction process of Azerbaijan. Finally we have a list of resources what of that we used in the thesis
The reconstruction process of Azerbaijan at the end of the Ottoman Empire (1918-1953)
Keywords: Tarih